Degradabilidade ruminal da matéria seca de folhas e colmo de genótipos de Cynodon spp. em quatro idades de rebrota - Oliveira, Euclides Reuter de; Monção, Flávio Pinto [UNESP]; Gordin, Caroline Libonato; Araújo Gabriel, Andréa Maria de; Lempp, Beatriz; Santos, Mariana Viegas dos; Reis, Sidnei Tavares dos; Moura, Lais Valenzuela (Univ Estadual Londrina, 2014)
This study aimed to evaluate ruminal kinetics of five genotypes of Cynodon (Tifton 85, Jiggs, Russell, Tifton 68 and Vaqueiro), harvested, aged 28, 48, 63 and 79 days with potential for haymaking. For in situ was used three steers with rumen cannulae, with incubation times of 96, 72, 48, 12, 6 and 0 hours. We used a randomized block design in split plots (grass as plots and subplots as the cut time) with three replications. Decreased (P < 0.05) to the levels of readily soluble fraction (fraction a), potentially degradable (fraction b) and the degradability of dry matter of the leaf and stem as there was increase in the maturity stage. For the degradability of dry matter of leaves, found daily reductions of 0.29; 0.47; 0.38; 0.39 and 0.26% for Tifton 85, Jiggs, Russell, Tifton 68 and Vaqueiro, respectively. It is recommended in the management of cutting regrowth age of 28 days from haymaking.

Objetivou-se avaliar a cinética ruminal de cinco genótipos do gênero Cynodon (Tifton 85, Jiggs, Russel, Tifton 68 e Vaqueiro), colhidos com idades de 28, 48, 63 e 79 dias com potencial para fenação. Para a degradabilidade in situ utilizaram três novilhos com cânulas ruminais, com tempos de incubação de 96, 72, 48, 12, 6 e 0 hora. Utilizou-se o delineamento em blocos casualizados em esquema de parcelas subdivididas (gramíneas como parcelas e idade ao corte como subparcelas) com três repetições. Houve redução (P<0,05) para os teores de fração prontamente solúvel (fração a), potencialmente degradável (fração b) e degradabilidade potencial da matéria seca da lâmina foliar e do colmo à medida que houve avanço no estádio de maturidade. Para degradabilidade potencial da matéria seca das folhas, constataram reduções diárias de 0,29; 0,47; 0,38; 0,39 e 0,26% para Tifton 85, Jiggs, Russel, Tifton 68 e Vaqueiro, respectivamente. Recomenda-se o manejo de corte na idade de rebrota de 28 dias para fenação.
Ruminal degradability of dry matter of leaves and stem of genotypes of Cynodon spp. four ages of regrowth
Keywords: Bromatologic composition degradation; Forage; Ruminant; Composição bromatológica; Degradação; Forragem; Ruminantes